Abnormal uptake related to the thyroid gland on somatostatin receptor-targeted PET imaging: reported prevalence and rate of thyroid malignancy and parathyroid adenomas - Sannia Mia Svenningsen Sjöstedt; Christoffer Holst Hahn; Åse Krogh Rasmussen; Peter Sandor Oturai; Per Karkov Cramon (Endocrine Connections, 2024)
Introduction: Incidental uptake within or adjacent to the thyroid gland is occasionally observed on somatostatin receptor-targeted PET imaging in patients with neuroendocrine neoplasms (NENs). The reported prevalence and clinical relevance of such findings are not well established. Materials and methods: We reviewed PET scan reports for all patients undergoing [68Ga]Ga-DOTA-TOC PET/CT or [64Cu]Cu-DOTA-TATE PET/CT in our department from 2018 to 2022. Scans reporting incidental uptake within or adjacent to the thyroid gland were reviewed post hoc to extract semi-quantitative scores of tracer uptake for the incidental lesions. We further extracted data from electronic patient charts, including cytology and histology. Results: A total of 3692 PET scans were performed on 1808 unique patients. Incidental abnormal thyroid uptake was reported in 42 of the 1808 patients, with thyroid malignancy identified in five of these 42 patients. Two patients had medullary thyroid cancers, two had neuroendocrine tumor metastases, and one had a renal clear cell carcinoma metastasis. Focal uptake in close relation to the thyroid gland, suggestive of parathyroid adenoma, was reported in another 13 of the 1808 patients, with biochemical hyperparathyroidism found in six of these 13 patients. Conclusion: In patients undergoing somatostatin receptor-targeted PET scans for evaluation of NENs, the prevalence of reported abnormal uptake within or adjacent to the thyroid gland was low. However, the rates of thyroid malignancy and parathyroid adenomas were substantial. Prospective studies are needed to determine the optimal diagnostic and therapeutic strategies for these incidental findings.